Astronomy hacks - Thompson, Robert Bruce (O'Reilly Media, 2005)
Astronomy Hacks begins the space exploration by getting you set up with the right equipment for observing and admiring the stars in an urban setting. Along for the trip are first rate tips for making most of observations. The hacks show you how to: Dark-Adapt Your Notebook Computer. Choose the Best Binocular. Clean Your Eyepieces and Lenses Safely. Upgrade Your Optical Finder. Photograph the Stars with Basic Equipment.
Keywords: Astronomy -- Observers' manuals; NATURE; Sky Observation; Astronomy; Handbooks and manuals